Stock Management Effectiveness In Manufacturing Industries: Insurance Perspective. (A Case Study Of Metal Furniture Nigeria Limited In Lagos, Nigeria) (International Journal of Scientific Research and Management (IJSRM), 2017)
Insurance is needful in everyday today activity. Insurance cuts across all fields of endeavor. It will bedisastrous running into a loss and not having insurance policy in place. In a nutshell, insurance gives anindividual, businessman or even the government of a nation a great deal of rest of mind because of theinsurance policy that is in place.Stock Management effectiveness in manufacturing industries isthe system ofrecording, forecasting and monitoring stores movement. Insurance can be defined as a risk transfermechanism whereby an individual, a business organization and even the government transfer theiruncertainty of loss unto the shoulder of the insurance company by paying a token amount known as thepremium. Thesignificant aims of any inventory management are: to avoid excessive and inadequate levels of inventories and maintain sufficient inventory for smooth production and sales operation. These aims maynot be achieved where there is fluctuation in supply and demand. The fluctuation brings in the risks ofrunning out of stock. Therefore this study will be useful to manufacturing companies in determining theminimum and maximum amount of stock to hold at every point in time. The study will also serve as areference point to researchers thatare willing to dwell in this area of study. The researcher adopted asimplerandom sampling technique for the study.The major tool that was employed in the collection ofprimary data for the study was questionnaire which was designed in such a way that it answered theresearch questions. The analysis reveals that Inventory Management has a positive influence onManufacturing Output. The result shows that effective Inventory Managementaccount for 82.4% in thevariation of manufacuring output, given the value of the R2 (0.824). Having analyzed the data and tested thehypothesis, the following are the findings deduced from the study. A reduction in the holding costs lead toproportionate increase in the profitability of a company. Well designed management policies help inmaintaining smooth operations with little or no hindrance in any activities. Prudent inventory managementis inevitable in manufacturing firms. Continuous inventory control curtails fraud more effectively than anannual stock-taking. Adequate finished goods to meet customers requirement avoid costs associated withstock-out. First-in-First-out (FIFO) method of valuing stocks is the most efficient way of valuing stockespecially when it comes to tracing the movement of stock. Inventory form a significant proportion of acompany’s assets. In conclusion, any manufacturing company stock and its effective management areobviously essential. Stocks make up a large proportion of manufacturing companies assets and therefore itseffective management should definitely contribute to the effective management of the business.